Amino Acids Profile of Five Leafy Vegetables Mainly Consumed in Western Côte d’Ivoire - Armel Fabrice, Zoro; Abdoulaye, Toure; Kouamé Appolinaire, Kouassi (European Scientific Journal, ESJ, 2022)
In tropical Africa, leafy vegetables are traditionally cooked and eaten as a relish together with a starchy staple food. To contribute to their wider utilization and valorization in food sector, five leafy vegetables consumed in Western Côte d’Ivoire were investigated for their amino acids composition. The leaves of Abelmoschus esculentus, Celosia argentea, Ipomea batatas, Manihot esculenta and Myrianthus arboreus were the five leafy vegetables studied. The samples of these five leafy vegetables in this study were collected at maturity in cultivated farmlands located at Dabou (Southern Côte d’Ivoire). Then, they were washed and oven dried at 60 °C during three days before ground. The amino acid content of the ground samples were analyzed by high performance liquid chromatography (HPLC) technical. The results were showed a significantly different (p ˂ 0.05) between amino acids contents of the five leafy vegetables. For a non-essential amino acids, all the five leaves studied were contained only proline with concentrations varying from 563.6 ± 1.08 to 1562.9 ± 1.88 mg/100 g. The two(2) other non-essential amino acids, arginine and tyrosine were detected only in leaves of C. argentea (1370.6 mg/100mg) and A. esculentus (1.70 mg/100mg) respectively. Concerning essential amino acids, only leucine was contained in all leafy vegetables with contents between 175.9 ± 0.56 and 9685.9 ± 5.14 mg/100 g. For the other essential amino acids, lysine was contained in leaves of C. argentea, I. batatas and M. arboreus with respectives concentrations of 266.7 ± 0.89 mg/100 g, 7225.9 ± 2.56 mg/100 g and 182.4 ± 0.66 mg/100 g. Tryptophane was quantified in leaves of A. esculentus and I. batatas with respectives levels of 1205.4 ± 1.86 mg/100g and 175.4 ± 0.84 mg/100g. Valine was detected in leaves of C. argentea and M. esculenta with respectives contents of 1069.4 ± 1.21 mg/100g and 1639.1 ± 1.39 mg/100g. Methionine was contained in leaf of C. argentea with level of 165.1 ± 0.61 mg/100g. The important concentration of amino acids revealed in leaves studied clearly would justify their consumption by Western Côte d’Ivoire populations. Therefore, exploitation of leafy vegetables could contribute food security of ivorian population.